IJCM_271A: Concerns and Considerations of Using Artificial Intelligence in Research: A Qualitative Exploration among Public Health Residents in Kolkata - Surendran Sujith (Wolters Kluwer Medknow Publications, 2024)
Background: The advent of Artificial Intelligence (AI) technologies has undeniably revolutionized various domains worldwide. AIs emergence has sparked significant interest from public health research domain due to its transformative potential. Thus, understanding its impact from the grass-root level: perspectives of the young research students, training in the field of public health is crucial. Objective: To explore the perceptions regarding the concerns and considerations for use of AI tools in research among students of a public health institute in Kolkata Methodology: A descriptive qualitative study was conducted among students pursuing MD degree. Focus group discussion (FGD) was done among the participants till data saturation was achieved. Audiogram, notes and sociogram were made during the FGD. Verbatims of the FGD were transcribed. Codes were obtained inductively and categorized. Data coding and analysis was done with NVivo 14 and data visualization was done using RAW graphs 2.0 Results: The various concerns that arouse were lack of trust, lack of knowledge, ethical issues, inadept to use and the impact of its use on the researcher. The young researchers also contemplated that there needs to be extensive training, ethical policy adaptation and self-checks required for its use. There is a growing body of thought to find solutions for the limitations in its use and its prospects. Conclusion: Most participants agreed to the fact their knowledge regarding its utilization was sub-optimal. There was a notable lack of trust in using AI tools for research among them. Addressing these challenges require a multifaceted approach involving extensive training initiatives, ethical policy adaptation to facilitate responsible AI use and a call for researchers to act as self-checks, while using AI in research